Intimate Partner Violence in Orthopaedic Surgery: Lessons Learned and Future Directions - Madden, Kim (My University, 2014)
The overarching theme of this thesis is to discuss the research to date on intimate partner violence (IPV) in orthopaedic surgery and to begin to study selected issues that have been understudied in orthopaedic surgery and IPV. This thesis outlines the current state of knowledge in the field of IPV and orthopaedic surgery and provides some insight into three selected “emerging issues” in the field which warrant future research including: education of orthopaedic surgeons and residents to reduce barriers and improve perceptions; IPV perpetrators; and outcomes for victims of IPV. The findings demonstrate that a short course on IPV for orthopaedic trainees led to an improvement and retention of knowledge three months after the course. IPV education should be integrated into training programs for orthopaedic surgeons. Our systematic review on IPV perpetrator factors indicates that using alcohol or drugs, experiencing child abuse, witnessing interparental aggression, low socioeconomic status, and psychological conditions like depression and anxiety were commonly associated with IPV perpetration. Perpetrator treatment programs should take into consideration modifiable and preventable factors that are associated with IPV perpetration. This thesis proposes a pilot prospective cohort study as the first step toward determining how experiences of IPV affect orthopaedic outcomes such as injury-related complications. The proposed study will determine feasibility and assist in the development a larger-scale multinational prospective cohort study that will engage health care professionals from around the world to increase awareness of how IPV affects patients’ musculoskeletal outcomes. In the past decade, the field of orthopaedic surgery has become more aware of the issue of IPV, but there are many questions that remain. Future research into the above issues will be an excellent first step to fully understanding the issue of IPV in orthopaedic patients, and may lead to improved support of victims of IPV in the future.
Keywords: intimate partner violence; orthopaedic surgery; systematic review; methods paper; medical education